NETWORK FORENSIC INVESTIGATION GUIDELINE FOR CAPTURING STEGANOGRAPHY FILES IN NETWORK TRAFFIC PACKETS - Ahmad Shukri Samsuddin, 1982-, author; Azizah Abdul Manaf, Prof.Dr., supervisor; Sekolah Informatiks Termaju (Kuala Lumpur : Universiti Teknologi Malaysia, 2016)
Thesis (Sarjana Sains (Jaminan Maklumat))-Universiti Teknologi Malaysia, 2015